An electronic counter for the radiation integrator (MAUSAM, 1974)
The paper describes a four-figure electric counter meant for use with the radiation integrator. The counter consists of decade counters made up of four flip-flops in cascade with gated feed back to eliminate the additional six states, and decoders made up of transistors. The display in on numicator tubes. The counter accepts a wide range of sharp pulses of amplitude 1 to 6v upto a frequency of 5 KHz.